2009
DOI: 10.1002/ajp.20694
|View full text |Cite
|
Sign up to set email alerts
|

The physical characteristics and usage patterns of stone axe and pounding hammers used by long‐tailed macaques in the Andaman Sea region of Thailand

Abstract: Stone hammering in natural conditions has been extensively investigated in chimpanzees and bearded capuchins. In contrast, knowledge of stone tool use in wild Old World monkeys has been limited to anecdotal reports, despite having known for over 120 years that Macaca fascicularis aurea use stone tools to process shelled foods from intertidal zones on islands in the Andaman Sea. Our report is the first scientific investigation to look at the stone tools used by these macaques. We observed they were skilled tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
209
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 241 publications
(229 citation statements)
references
References 40 publications
12
209
0
8
Order By: Relevance
“…We have seen from direct observations of macaque tool-use behaviour that a small proportion of macaques have idiosyncratic dependencies on specific tool features and reliably use the same kind of tool. However, our observations also show that a much larger proportion of macaques on Piak Nam Yai use a range of tool sizes, which seem to be in accordance with what we have found in this study (M. D. Gumert 2009Gumert -2012, unpublished data). Additionally, we did not experimentally separate the natural association between size and mass in our study, and thus cannot make conclusions on which of these two physical dimensions the macaques attended to during selection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We have seen from direct observations of macaque tool-use behaviour that a small proportion of macaques have idiosyncratic dependencies on specific tool features and reliably use the same kind of tool. However, our observations also show that a much larger proportion of macaques on Piak Nam Yai use a range of tool sizes, which seem to be in accordance with what we have found in this study (M. D. Gumert 2009Gumert -2012, unpublished data). Additionally, we did not experimentally separate the natural association between size and mass in our study, and thus cannot make conclusions on which of these two physical dimensions the macaques attended to during selection.…”
Section: Discussionsupporting
confidence: 92%
“…We have determined that 88% of all adolescents and adults living on Piak Nam Yai use stones daily to process foods [33], which amounts to ca 20% of their total activity when on the shore, and 40% of their coastal foraging time budget (M.D. Gumert 2009Gumert -2012, unpublished data).…”
Section: (B) Macaque Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimpanzees increased use of tools during periods of fruit scarcity at Bossou, Guinea [31]. Additional suggestions of tool use during times of necessity have been asserted for bearded capuchins in northeastern Brazil [45] and long-tailed macaques in Thailand [43], but the necessity hypothesis was not explicitly tested in these particular studies. There are also situations in which it is difficult to differentiate responses to necessity and opportunity.…”
Section: Introductionmentioning
confidence: 95%
“…Most of these studies documented the use of tools only in a limited number of individuals and often the reports are anecdotal [6]. More recently, it has been reported that long-tailed macaques of a wild population in Thailand regularly use stones as tools to crack shelled seafood [7]. Despite this example, there is still a general agreement in the scientific community that macaques are not skilled tool users.…”
Section: Introductionmentioning
confidence: 99%